High visibility of outdoor tobacco advertisements around health facilities in East Java, Indonesia: a geospatial analysis (Medical Journal of Indonesia, 2021)
BACKGROUND Indonesian tobacco control initiatives are minimal despite having the second-highest adult male smoking prevalence in the world, with less than 10% of districts/cities banning outdoor tobacco advertisements. This research aimed to provide evidence on the presence of outdoor tobacco advertisements near health facilities in Surabaya where there is no outdoor advertising ban. METHODS Data collection was carried out in Surabaya from October to November 2018. Data of government (public) and private health facilities were obtained from the city health office. Two spatial data analyses were carried out: a buffer analysis near the healthcare facilities and an advertisement hotspot analysis using ArcMap 10.6. RESULTS From 308 tobacco advertisements that were identified, there were billboards (63%), banners (31%), and videoboards (7%). Of 142 public and 1,242 private health facilities in Surabaya, 26% and 31% had advertisements within 300 m and 63% and 70% were within advertisement hotspots, respectively. Furthermore, 5% of advertisements were within 300 m from public health facilities and 21% of them were within 300 m from private health facilities. CONCLUSIONS Outdoor tobacco advertisements were widespread throughout the city, prominently around public and private health facilities.